Switch of NAD Salvage to de novo Biosynthesis Sustains SIRT1-RelB-Dependent Inflammatory Tolerance - Zhang, Jingpu; Tao, Jie; Ling, Yun; Li, Feng; Zhu, Xuewei; Xu, Li; Wang, Mei; Zhang, Shuye; McCall, Charles E.; Liu, Tie Fu (Frontiers in Immunology, 2019)
A typical inflammatory response sequentially progresses from pro-inflammatory, immune suppressive to inflammatory repairing phases. Although the physiological inflammatory response resolves in time, severe acute inflammation usually sustains immune tolerance and leads to high mortality, yet the underlying mechanism is not completely understood. Here, using the leukemia-derived THP-1 human monocytes, healthy and septic human peripheral blood mononuclear cells (PBMC), we report that endotoxin dose-dependent switch of nicotinamide adenine dinucleotide (NAD) biosynthesis pathways sustain immune tolerant status. Low dose endotoxin triggered nicotinamide phosphoribosyltransferase (NAMPT)-dependent NAD salvage activity to adapt pro-inflammation. In contrast, high dose endotoxin drove a shift of NAD synthesis pathway from early NAMPT-dependent NAD salvage to late indoleamine 2,3-dioxygenase-1 (IDO1)-dependent NAD de novo biosynthesis, leading to persistent immune suppression. This is resulted from the IDO1-dependent expansion of nuclear NAD pool and nuclear NAD-dependent prolongation of sirtuin1 (SIRT1)-directed epigenetics of immune tolerance. Inhibition of IDO1 activity predominantly decreased nuclear NAD level，which promoted sequential dissociations of immunosuppressive SIRT1 and RelB from the promoter of pro-inflammatory TNF- gene and broke endotoxin tolerance. Thus, NAMPT-NAD-SIRT1 axis adapts pro-inflammation, but IDO1-NAD-SIRT1-RelB axis sustains endotoxin tolerance during acute inflammatory response.